Chemical and Biological Stability under Forced Degradation and Accelerated Storage Conditions of the Anti-Acne Formulation of Pra-Sa-Mang-Khud Ethanolic Extract - Phumlek, Kalyarut; Itharat, Arunporn; Saesiw, Ubonwan; Pipatrattanaseree, Weerachai; Piwngam, Krit; Sookdee, Papawee; Davies, Neal M. (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Pra-Sa-Mang-Khud (PSM) formula is the mixture of Garcinia mangostana pericarp and Ha-Rak remedy developed for acne treatment. However, the chemical and biological stability of PSM extract is necessary for an optimal manufacturing process. Therefore, this study was aimed to investigate the stability of PSM ethanolic extract under forced degradation and accelerated storage conditions. Methods: Thermal degradation, moisture hydrolysis, acid hydrolysis, alkaline hydrolysis, and oxidation were performed in forced degradation studies. In addition, PSM extract was kept in accelerated storage conditions at 40 ± 2ºC with 75 ± 5% RH for 6 months. Finally, PSM extracts under forced degradation and accelerated storage conditions were evaluated for α-mangostin and pectolinarigenin contents by high performance liquid chromatography and antibacterial activity against C. acnes. Results: PSM extract under acid hydrolysis and oxidation conditions had significantly degraded α-mangostin content and reduced anti-C. acnes activity. In contrast, the treatments with high temperature, moisture hydrolysis, and alkaline hydrolysis increased α-mangostin content. For accelerated storage conditions, α-mangostin content, pectolinaligenin content, and anti-C.acnes activity were shown to be stable in all samples. Conclusions: Avoiding preparation in an acidic environment is essential for optimal PSM extract efficacy. Moreover, an antioxidant agent that prevents degradation is necessary. Both the hot and cold processes can be effectively used to prepare the product containing PSM extract. PSM extract can have a tentative shelf-life of two years due to its demonstrated stability under accelerated storage conditions.